Accelerated differentiation of melanocyte stem cells contributes to the formation of hyperpigmented maculae. Issue 9 (September 2014) - Yamada, Takaaki; Hasegawa, Seiji; Inoue, Yu; Date, Yasushi; Arima, Masaru; Yagami, Akiko; Iwata, Yohei; Takahashi, Masayuki; Yamamoto, Naoki; Mizutani, Hiroshi; Nakata, Satoru; Matsunaga, Kayoko; et al.
Abstract It has been reported that the abnormal regulation of melanocyte stem cells (McSCs) causes hair greying; however, little is known about the role of McSCs in skin hyperpigmentation such as solar lentigines (SLs). To investigate the involvement of McSCs in SLs, the canonical Wnt signalling pathway that triggers the differentiation of McSCs was analysed in UVB‐induced delayed hyperpigmented maculae in mice and human SL lesions. After inducing hyperpigmented maculae on dorsal skin of F1 mice of HR‐1× HR/De, which was formed long after repeated UVB irradiation, the epidermal Wnt1 expression and the number of nuclear β‐catenin‐positive McSCs were increased as compared to non‐irradiated control mice. Furthermore, the expression of dopachrome tautomerase (Dct), a downstream target of β‐catenin, was significantly upregulated in McSCs of UVB‐irradiated mice. The Wnt1 expression and the number of nuclear β‐catenin‐positive McSCs were also higher in human SL lesions than in normal skin. Recombinant Wnt1 protein induced melanocyte‐related genes including Dct in early‐passage normal human melanocytes (NHEMs), an in vitro McSC model. These results demonstrate that the canonical Wnt signalling pathway is activated in SL lesions and strongly suggest that the accelerated differentiation of McSCs is involved in SL pathogenesis.